Direct costs associated with adverse events of systemic therapies for advanced melanoma: Systematic literature review. Issue 31 (August 2018) - Copley-Merriman, Catherine; Stevinson, Kendall; Liu, Frank Xiaoqing; Wang, Jingshu; Mauskopf, Josephine; Zimovetz, Evelina A.; Chmielowski, Bartosz
Abstract: Background: Treatments for advanced melanoma are associated with different adverse events (AEs), which may be costly to manage. This study aimed to evaluate direct costs associated with managing treatment-related AEs for advanced melanoma through a systematic literature review. Methods: Systematic searches were conducted of the PubMed, Embase, Cochrane, BIOSIS, and EconLit medical literature databases to identify studies providing estimates of direct costs and health care resource utilization for the management of AEs of melanoma treatments, published between January 1, 2007, and February 23, 2017. Gray literature searches also were conducted. Studies reporting direct costs for patients with advanced melanoma that were published in English between 2007 and 2017 were eligible. Studies were systematically screened in 2 phases by 2 independent reviewers. Study design details and data on direct costs by country were extracted. Results: Seven studies evaluating the cost of AEs in patients with advanced melanoma were included; most estimated the costs for grade 3 or 4 events. In a United States study, monthly AE costs constituted 36.9% of overall health care costs for dacarbazine, 30.3% for paclitaxel, 9.2% for temozolomide, 6.4% for vemurafenib, and 4.0% for ipilimumab. A multicountry study found the greatest cost per event to be for grade 3 or 4 AEs associated with ipilimumab, including colitis (A1471 [Australia]–[Euro sign]3313 [France]) and diarrhea (£2836 [United Kingdom]), and chemotherapy (neutropenia/leukopenia in Germany [[Euro sign]1744] and Italy [[Euro sign]804]). Across studies, cost drivers for the most expensive AEs to manage were requiring hospitalization or use of expensive outpatient medications and/or procedures (eg, erythropoietin and blood transfusions for anemia). Some currently available therapies were not available during the research period, and their associated AEs are not reflected. Results may not be comparable across countries. For some studies, resource-use estimates reflect practice patterns from a limited number of centers, limiting generalizability. Conclusion: Costs for managing each type of AE associated with the treatment of advanced melanoma are substantial. Effective treatments with improved safety profiles may help reduce total AE management costs. Abstract : Supplemental Digital Content is available in the text